A method for characterizing shale pore structure anisotropy based on small-angle neutron scattering
The method of treating shale samples through small angle neutron scattering method solves the problem of ignoring the anisotropy of the shale pore structure in the prior art, and realizes the accurate quantitative characterization of the anisotropy of the pore structure of shale, which is of great significance to oil Store fine evaluation and effective mining.
Patent Information
- Application Number
- CN202210153346.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-02-18
AI Technical Summary
The prior art ignores its anisotropy when dealing with shale pore structures, resulting in large errors and the inability to accurately characterize the orientation of shale pore structures.
The shale sample was experimented with small angle neutron scattering method to obtain the ellipsoid anisotropic two-dimensional scattering profile, and the integral region division, calculate the scattering intensity and draw the non-uniform distribution map, and select the maximum and minimum scattering intensity regions to obtain the one-dimensional scattering curves, corrected and fitted, quantitatively characterize the anisotropy of pore structures.
Accurate quantitative characterization of the anisotropy of shale pore structure is realized, sample processing flow and data processing methods are optimized, and effective means to explore the advantageous channels of oil and gas migration, which is of great significance to the fine evaluation and effective mining of reservoirs.
Smart Images

Figure CN114577832B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of unconventional oil and gas geological experiments, and in particular to a method for characterizing the anisotropy of shale pore structure based on small-angle neutron scattering. Background Art
[0002] Natural gas has become an effective alternative energy source to coal and crude oil due to its low carbon emission characteristics. At present, due to the rapid growth of shale gas production, unconventional natural gas has become increasingly important. However, as a source rock, shale has a complex pore structure, ultra-low porosity and permeability, which makes the oil reservoir exploitation process encounter many challenges. Among them, the nanoscale pore structure in the shale matrix is crucial for predicting long-term natural gas production. The anisotropic shale pore structure not only affects the adsorption capacity of natural gas, but also directly affects the diffusion capacity of gas during the process of natural gas extraction or carbon dioxide storage. Therefore, the anisotropy of shale pore structure is the key to shale gas development and carbon dioxide storage in shale reservoirs.
[0003] In recent years, small-angle neutron scattering, as a type of ray detection method, has been effectively applied to shale. It can determine the nanoscale pore structure of shale samples without damaging the samples. However, ellipsoidal scattering cross sections are often encountered in experimental data processing, which means that the sample has significant anisotropy, that is, the pore structure has obvious orientation, but this anisotropy is ignored in the processing process, and the data is directly radially averaged. This has little effect on isotropic samples, but there will be large errors for anisotropic samples, and it is impossible to obtain data on the anisotropy of the sample's pore structure. Summary of the invention
[0004] The main technical problem to be solved by the present invention is to provide a method for characterizing the anisotropy of shale pore structure. In order to solve the above problem, the present invention provides a method for characterizing the anisotropy of shale pore structure based on small-angle neutron scattering. The method comprises the following steps:
[0005] S1: prepare the shale sample to be tested;
[0006] S2: performing a small-angle neutron scattering experiment on the shale sample to be tested to obtain an ellipsoidal anisotropic two-dimensional scattering profile;
[0007] S3: dividing the ellipsoidal anisotropic two-dimensional scattering profile into integral regions, calculating the scattering intensity at each azimuth according to the integral regions, and drawing a non-uniform distribution diagram of the scattering intensity relative to the azimuth;
[0008] S4: selecting a maximum scattering intensity region and a minimum scattering intensity region in the non-uniform distribution map, and using SasView software to obtain one-dimensional scattering curves corresponding to the two regions respectively;
[0009] S5: Correcting and fitting the two one-dimensional scattering curves to obtain pore structure information of the shale sample to be tested in two different directions, parallel to the bedding and perpendicular to the bedding;
[0010] S6: Quantitatively characterize the anisotropy of the pore structure of the shale sample to be tested by comparing the pore structure information in two different directions.
[0011] Preferably, in step S1, the step of preparing the shale sample to be tested comprises:
[0012] The shale sample to be tested was processed into square slices with a thickness of 0.5 mm and a length and width of 1 cm along the direction perpendicular to the bedding by a cutting machine, and the front and back surfaces of the square slices were polished by a grinding and polishing machine.
[0013] Preferably, in step S2, before performing a small-angle neutron scattering experiment on the shale sample to be tested, the step further includes:
[0014] The square slices are dried in an oven at a temperature of 60-80° C. for at least 48 hours until the weight of the square slices does not change.
[0015] Preferably, in step S2, the small-angle neutron scattering experiment is performed in a sample chamber.
[0016] Preferably, in step S2, during the process of performing the small-angle neutron scattering experiment on the shale sample to be tested, the process further includes: recording sample parameters and test parameters; the sample parameters and test parameters include: sample thickness, test time, and dark current intensity.
[0017] Preferably, step S3 comprises:
[0018] Importing the ellipsoidal anisotropic two-dimensional scattering profile into SasView software, dividing the scattering profile within the corresponding scattering vector range into an integral region;
[0019] Calculate the scattering intensity at each azimuth angle based on the integration area;
[0020] A non-uniform distribution diagram of the scattering intensity relative to the azimuth angle is drawn according to the corresponding relationship between the scattering intensity and the azimuth angle.
[0021] Preferably, in step S4, the two regions corresponding to the maximum scattering intensity region and the minimum scattering intensity region are 0°±10° and 90°±10° respectively.
[0022] Preferably, in step S4, the step of using SasView software to respectively obtain one-dimensional scattering curves corresponding to the two regions comprises:
[0023] The two selected areas were sector-averaged using SasView software to obtain the one-dimensional scattering curves corresponding to the two areas.
[0024] Preferably, step S5 comprises:
[0025] Performing intensity correction, background subtraction and normalization processing on each of the one-dimensional scattering curves to obtain processed data;
[0026] The processed data are imported into the Irena plug-in in the Igor Pro software, and the non-negative least squares method is used for fitting to obtain the pore structure information of the shale sample to be tested in two directions.
[0027] Preferably, in step S6, the pore structure information includes: porosity, pore density, fractal dimension and pore size distribution.
[0028] The technical solution provided by the present invention has the following beneficial effects:
[0029] The present invention provides a new experimental technology for characterizing the anisotropy of shale pore structure. The shale sample to be tested is subjected to a small-angle neutron scattering experiment to obtain an ellipsoidal anisotropic two-dimensional scattering profile, and then the integral region is divided to calculate the scattering intensity to obtain a non-uniform distribution diagram of the scattering intensity relative to the azimuth angle; the maximum scattering intensity area and the minimum scattering intensity area are selected and the corresponding one-dimensional scattering curve is obtained; the one-dimensional scattering curve is corrected and fitted to obtain the pore structure information of the shale sample to be tested in two different directions; by comparing the pore structure information in two different directions, the anisotropy of the pore structure is quantitatively characterized. The present invention optimizes the processing flow of the sample to be tested, deepens the processing means of experimental data, quantitatively characterizes the anisotropy of the shale pore structure, provides an effective means for exploring the dominant channel for oil and gas migration, and is of great significance for the fine evaluation and effective exploitation of oil reservoirs. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The present invention will be further described below with reference to the accompanying drawings and embodiments, in which:
[0031] Figure 1 It is a schematic flow chart of a method for characterizing shale pore structure anisotropy based on small-angle neutron scattering provided in an embodiment of the present invention;
[0032] Figure 2 is a schematic diagram of a method for preparing a shale sample to be tested provided in an embodiment of the present invention;
[0033] Figure 3 It is a schematic diagram of a small-angle neutron scattering experiment and a sector-shaped average area division provided by an embodiment of the present invention;
[0034] Figure 4is a non-uniform distribution diagram of scattering intensity relative to azimuth provided by an embodiment of the present invention;
[0035] Figure 5 is a one-dimensional scattering curve diagram provided by an embodiment of the present invention;
[0036] Figure 6 This is a pore size distribution diagram provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0037] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described in detail with reference to the accompanying drawings.
[0038] A method for characterizing the anisotropy of shale pore structure based on small-angle neutron scattering in the present invention is implemented based on the following principles:
[0039] Neutron scattering is caused by the electric field of the incident light beam causing the electrons in the sample to oscillate, and then radiate neutron rays of different wavelengths to the surroundings. Usually, the scattering data detected by the small-angle neutron scattering method occurs in the range of scattering angle ≤5°, so it is called small-angle neutron scattering. The scattering of neutron rays of the same wavelength measured experimentally is called Thompson scattering, also known as coherent scattering or elastic scattering. The uneven distribution of electron density in the sample leads to the optical path difference of the scattered light, resulting in a phase difference between the waves, which leads to interference of the scattered waves. It is assumed that the shale matrix has two-phase characteristics, which refers to a matrix with a precisely known electron density and pores with random shapes, sizes and spatial distributions, which are filled with air or shale gas. The difference in electron density between the shale matrix and the pores leads to neutron ray scattering. During the experiment, the main data measured is the data of the scattering intensity I(Q) changing with the scattering vector Q. The definition of the scattering vector Q can be expressed by formula (1), where λ is the neutron beam wavelength and θ is the scattering angle:
[0040] Q=4πλ -1 sinθ (1)
[0041] During the data analysis, the high-Q region corresponds to small pores, the low-Q region corresponds to large pores, and the calculation method uses the polydisperse sphere model (PDSM) to describe the spatial distribution of the dispersion (pores).
[0042] Please refer to Figure 1 The embodiment of the present invention provides a method for characterizing the anisotropy of shale pore structure based on small-angle neutron scattering, comprising the following steps:
[0043] S1: Prepare the shale sample to be tested. The specific operation steps are as follows: select the shale sample to be tested, cut the shale sample rock into blocks perpendicular to the bedding direction using a cutting machine, and cut a square slice with a thickness of 0.5 mm and a length and width of 1 cm (such as Figure 2As shown in the figure, the front and back surfaces of the square slices are polished with a grinder and polisher to reduce the influence of the rough surface on the experimental accuracy, and then the square slices are placed in an oven for drying.
[0044] In the above process, it should be noted that the square slices must be perpendicular to the bedding direction. In particular, the temperature of the oven is set to 60-80°C. Drying at this temperature can effectively remove the influence of water in the shale sample. The drying time is set to at least 48 hours until the sample quality no longer changes.
[0045] S2: The prepared shale samples were subjected to small-angle neutron scattering experiments. The experiment was conducted on the general SANS instrument at the Spallation Neutron Source of the Institute of High Energy Physics in Dongguan, China. First, the staff needed to debug the experimental parameters of the experimental instrument, including detector efficiency correction, wavelength correction, background correction, transmittance measurement, etc. During the test, the distance from the sample to the receiver was fixed at 4m. By receiving incident neutron beams of different wavelengths, The test data covers the scattering vector Q by range, and during the test, the sample parameters and test parameters need to be recorded, including sample thickness, test time, dark current intensity, etc., for subsequent experimental data processing. After the experiment is completed, the ellipsoidal anisotropic two-dimensional scattering profile of the shale sample to be tested is obtained.
[0046] S3: Divide the ellipsoidal anisotropic two-dimensional scattering profile obtained in S2 into integral regions and perform sector average integration, such as Figure 3 Then, according to the calculation results, a non-uniform distribution diagram of the scattering intensity of the scattering profile relative to the azimuth angle is drawn (as shown in Figure 4 shown).
[0047] S4: Select the maximum scattering intensity area and the minimum scattering intensity area in the non-uniform distribution diagram. According to the sample being perpendicular to the bedding direction, this area is usually 90° (±10°) and 0° (±10°). After performing sector averaging, a one-dimensional scattering curve is obtained (e.g. Figure 5 shown).
[0048] S5: The two one-dimensional scattering curves obtained in step S4 are subjected to intensity correction, background subtraction and normalization processing, and then the processed data are subjected to model fitting using the Irena plug-in in the Igor Pro software to obtain the pore structure information of the sample in two different directions: parallel to the bedding (corresponding to the maximum scattering intensity area) and perpendicular to the bedding (corresponding to the minimum scattering intensity area).
[0049] Specifically, during the small-angle neutron scattering data processing, S5 determined that the pore diameter range that can be characterized by this small-angle neutron scattering experiment is 1 to 128 nm based on the range of scattering vectors Q covered by the test and the formula r≈2.5 / Q between the pore radius (r) and the scattering vector (Q). The pore structure of the sample was calculated using the least squares method to obtain the pore structure information of the sample, where the pore size distribution is as follows: Figure 6 shown.
[0050] S6: Compare the pore structure information of the shale sample to be tested in two directions to obtain the anisotropy of the pore structure of the shale sample to be tested.
[0051] In this embodiment, Longmaxi Formation shale samples were selected for experiments, and smooth shale slice samples perpendicular to the bedding with a thickness of 0.5 mm, a length and a width of 1 cm were prepared, and then dried in an oven for pretreatment, and the drying temperature was set to 60°C, and the drying time was more than 48 hours until the mass change rate was below 0.001. After the treatment, a small-angle neutron scattering experiment was performed on the shale slice sample to obtain an ellipsoidal anisotropic two-dimensional scattering profile, and the data was sector-averaged and integrated using SasView to draw a non-uniform distribution diagram of the scattering intensity relative to the azimuth angle, and 0° (±10°) and 90° (±10°) were selected to perform integral calculations to obtain a one-dimensional scattering curve composed of one-dimensional data.
[0052] The two one-dimensional scattering curves were subjected to intensity correction, background subtraction and normalization to obtain the processed data, which were then imported into the Irena plug-in in the Igor Pro software. The scattering data were fitted by the non-negative least squares method to calculate the pore structure information of the shale samples in two directions.
[0053] In this embodiment, the experimental results are shown in Table 1.
[0054] Table 1: Pore structure information of shale samples in two directions
[0055]
[0056] It can be seen that in this embodiment, the porosity of the structure perpendicular to the bedding is 1.3%, while the porosity of the structure parallel to the bedding is 3.3%, which is more than twice the former, and the pore density parallel to the bedding is also much greater than the pore density perpendicular to the bedding. This shows that as the burial depth of the formation increases, the pores will flatten along the direction parallel to the bedding as the formation is compacted, and a large number of microcracks along this direction are generated. The fractal dimension parallel to the bedding direction is 2.27, while the fractal dimension perpendicular to the bedding direction is 2.52, indicating that the pore surface of the structure parallel to the bedding direction is smoother and flatter than that perpendicular to the bedding direction. Figure 6It can be seen that the pore size distribution in both directions is mainly concentrated below 20nm, and this part of the scale mainly exists in the organic matter network, indicating that the organic pores in shale have more obvious anisotropy. The pores above 20nm are mainly inorganic pores. Since pyrite and quartz in the mineral components have good support, the inorganic pores are less affected by the compaction of the formation, and the anisotropy is not obvious compared with the organic pores.
[0057] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or system. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or system including the element.
[0058] The serial numbers of the embodiments of the present invention are for descriptive purposes only and do not represent the superiority or inferiority of the embodiments. In a unit claim that lists several means, several of these means may be embodied by the same hardware item. The use of the words first, second, and third, etc. does not indicate any order and these words may be interpreted as identifiers.
[0059] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for characterizing the anisotropy of shale pore structure based on small-angle neutron scattering, characterized in that: The following steps are involved: S1: Preparation of shale samples to be tested: Processing the shale sample to be tested into square slices along a direction perpendicular to the bedding direction using a cutting machine; S2: performing a small-angle neutron scattering experiment on the shale sample to be tested to obtain an ellipsoidal anisotropic two-dimensional scattering profile; S3: importing the ellipsoidal anisotropic two-dimensional scattering profile into SasView software, and dividing the scattering profile within the corresponding scattering vector range into an integral region; Calculate the scattering intensity at each azimuth angle based on the integration area; Draw a non-uniform distribution diagram of scattering intensity relative to azimuth angle according to the corresponding relationship between the scattering intensity and the azimuth angle; S4: selecting the maximum scattering intensity region and the minimum scattering intensity region in the non-uniform distribution map, and using SasView software to perform sector averaging on the two selected regions respectively to obtain one-dimensional scattering curves corresponding to the two regions; In step S4, the maximum scattering intensity region is 90°±10°, and the minimum scattering intensity region is 0°±10°; S5: performing intensity correction, background subtraction and normalization processing on each of the one-dimensional scattering curves to obtain processed data; importing the processed data into the Irena plug-in of the Igor Pro software, and fitting the data using the non-negative least squares method to obtain the pore structure information of the shale sample to be tested in two directions parallel to the bedding and perpendicular to the bedding; S6: Quantitatively characterize the anisotropy of the pore structure of the shale sample to be tested by comparing the pore structure information in two different directions.
2. The method for characterizing shale pore structure anisotropy based on small-angle neutron scattering according to claim 1, characterized in that: In step S1, the front and back surfaces of the square slice are polished by a grinder and polisher.
3. The method for characterizing shale pore structure anisotropy based on small-angle neutron scattering according to claim 1, characterized in that: In step S2, before performing a small-angle neutron scattering experiment on the shale sample to be tested, the method further includes: Drying the square slices, with the oven temperature set at 60-80° C. for at least 48 hours, until the weight of the square slices does not change; In step S2, the small-angle neutron scattering experiment is performed in a sample chamber; In step S2, during the process of performing the small-angle neutron scattering experiment on the shale sample to be tested, the process further includes: recording sample parameters and test parameters; The sample parameters and test parameters include: sample thickness, test time and dark current intensity.
4. The method for characterizing shale pore structure anisotropy based on small-angle neutron scattering according to claim 1, characterized in that: In step S6, the pore structure information includes: porosity, pore density, fractal dimension and pore size distribution.
Citation Information
Patent Citations
Method for representing water absorption expansibility of shale microstructure by using small-angle neutron scattering experiment
CN113484348A